Diminished mental- and physical function and lack of social support are associated with shorter survival in community dwelling older persons of Botswana - Molebatsi Robert M; Wilson Adrian O; Clausen Thomas; Holmboe-Ottesen Gerd (BMC, 2007)
Abstract Background Mortality rates for older persons in Botswana have been unavailable and little is known of predictors of mortality in old age. This study may serve as a precursor for more detailed assessments. The objective was to assess diminished function and lack of social support as indicators of short term risk of death. Methods A national population based prospective survey was undertaken in Botswana; twelve rural areas and three urban centers were included. 372 community-dwelling persons aged sixty years and over, were included; 265 were followed-up. Sixteen subjects were deceased at follow-up. Subjects were interviewed and clinically assessed at home. Measures of cognitive function, depression and physical function and sociodemographic information were collected. Subjects were followed-up at average 6.8 months after baseline. Results Overall mortality rate was 10.9 per 100 person years. Age-adjusted odds ratios (OR) for death during follow-up were; 4.2 (CI 1.4-12.5) and 3.6 (CI 1.0-12.7) for those with diminished physical- and cognitive function, respectively. Indicators of limited social support; household with only 1 or 2 persons and eating alone, yielded age adjusted ORs of 4.3 (CI 1.5-12.5) and 6.7 (CI 2.2-20), respectively, for death during follow-up. Conclusion Older community dwelling persons with diminished cognitive- or physical function, solitary daily meals and living in a small household have a significantly increased risk of rapid deterioration and death. Health policy should include measures to strengthen informal support and expand formal service provisions to older persons with poor function and limited social networks in order to prevent premature deaths.